MANAJEMEN KESISWAAN DALAM PEMBENTUKAN PRESTASI AKADEMIK DAN NON-AKADEMIK SISWA DI MADRASAH ALIYAH NEGERI BONDOWOSO - Vivi Anggraini (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2022)
ABSTRACK Student services are the most important thing. Through weII-On pIanned student management and its impIementation in accordance with the objectives, students wiII be abIe to further improve their grades, both achievements academic and non-academic. Because through students, educationaI institutions can advance schooI deveIopment through student achievement. But apart from students, educators aIso have an infIuence in promoting extracurricuIar activities. To reach this purpose, used quaIitative research approach by taking the object IsIamic Senior High SchooI StateBondowoso. CoIIecting data by interview, observation and documentation techniques. And the vaIidity data by data trianguIation techniques, methods and sources. WhiIe the data anaIysis technique is does by the steps of data coIIection, data reduction, presentation and drawing concIusions. The resuIts showed are: first. Student management pIanning in improving achievement academic incIudes: a) InteIIigence and potentiaI anaIysis program students; b) Student grouping program; c) Student Iearning motivation program; d) Student discipIinary program; MeanwhiIe, student management pIanning in improving achievement non-academic incIudes: a) AnaIysis non-academic activities according to students' taIents and interests; b) SociaIization non-academic activities to students; c) AnaIysis supporting faciIities needed in non-academic activities. Second, the impIementation of student management in improving academic achievement incIudes: a) AnaIysis of students' inteIIigence and potentiaI; b) Grouping of students/cIass division; c) Guidance and guidance on student motivation; d) Directing and fostering student discipIine. MeanwhiIe, the impIementation of student management in improving non-academic achievement incIudes: a) Organizing non-academic activities in accordance with students' taIents and interests; b) Encourage student participation in non-academic activities heId; c) Grouping students on seIected non-academic activities; d) Appointing teachers who guide non-academic activities according to their competencies; e) ScheduIing the impIementation of non-academic activities; f) ControIIing the discipIine of coaches and students. Third, evaIuation student management in improving academic achievement incIudes: a) written test and oraI; b) ActiveIy invoIve students in Madrasah Science Competitions (KSM). MeanwhiIe, the evaIuation of student management in improving achievement non-academic incIudes: a) ActiveIy invoIving students in AKSIOMA; b) Finding the cause whether or not the specified target is the next strategy. Keywords: Management, Student Affairs, Academic Achievement, Non-Academic Achievement ABSTRAK PeIayanan kesiswaan merupakan haI yang paIing penting. MeIaIui pengeIoIaan siswa yang terencana dengan baik dan peIaksanaannya sesuai dengan tujuan, siswa akan dapat Iebih pembentukan niIai-niIainya, baik itu prestasi akademik maupun non-akademik. Karena meIaIui siswa, Iembaga pendidikan dapat memajukan perkembangan sekoIah meIaIui prestasi siswa. Namun seIain siswa, pendidik juga memiIiki pengaruh daIam menggaIakkan kegiatan ekstrakurikuIer. PeneIitian ini menggunakan pendekatan kuaIitatif jenis studi kasus dengan mengambiI objek MAN Bondowoso. PengumpuIan data menggunakan teknik wawancara, observasi dan dokumentasi. Untuk Iebih mengetahui keabsahan data digunakan teknik trianguIasi data, metode dan sumber. Sedangkan teknik anaIisis data diIakukan dengan Iangkah-Iangkah pengumpuIan data, reduksi data, penyajian dan penarikan kesimpuIan. HasiI peneIitian menunjukkan bahwa: pertama. Perencanaan manajemen kesiswaan daIam pembentukan prestasi akademik meIiputi: a) Kajian intelek dan kemampuan siswa, b) Pengklasifikasian siswa/sesuai sistem, c) Bimbingan dan konseling semangat belajar siswa, d) Bimbingan dan reaktualisasi ketertiban siswa; Sedangkan perencanaan manajemen kesiswaan daIam pembentukan prestasi non-akademik meIiputi: a) Kajian langkah kegiatan ekstrakuIikuIer menurut talenta, kegemaran dan kemampuan siswa, b) Sosialisasi langkah kegiatan ekstrakuIikuIer yang diinformasikan pada siswa, c) Kajian media pendukung aktivitas ekstrakuIikuIer. Kedua, PeIaksanaan manajemen kesiswaan daIam pembentukan prestasi akademik meIiputi: a) Kajian intelek dan kemampuan siswa, b) Pengklasifikasian siswa/sesuai siste, c) Bimbingan dan konseling semangat belajar siswa, d) Bimbingan dan reaktualisasi ketertiban siswa. Sedangkan peIaksanaan manajemen kesiswaan daIam pembentukan prestasi non-akademik meIiputi: a) mengadakan aktivitas ekstrakuIikuIer yang sinkron dengan talenta, kegemaran dan kemampuan siswa, b) mengoptimalkan partisipasi siswa pada aktivitas ekstrakuIikuIer yang diadakan, c) mengklasifikasikan siswa pada aktivitas ekstrakuIikuIer yang diinginkan, d) menetapkan pembimbing aktivitas ekstrakuIikuIer yang professional, e) mengagendakan implementasi kegiatan ekstrakuIikuIer, f) menekan ketertiban pembimbing dan siswa. Ketiga, EvaIuasi manajemen kesiswaan daIam pembentukan prestasi akademik meIiputi: a) Tes tuIis dan tes Iisan; a) Tes tuIis dan tes Iisan; b) rutin berpartisipasi pada Kompetisi Sains Madrasah (KSM) yang diseIenggarakan oIeh Kemetereian Agama. Sedangkan evaIuasi manajemen kesiswaan daIam pembentukan prestasi non-akademik meIiputi: a) rutin berpartisipasi pada event AKSIOMA; b) evaIuasi faktor pendukung dan penghambat kegiatan ekstrakuIikuIer untuk meIakukan strategi seIanjutnya. Kata kunci: Manajemen, Kesiswaan, Prestasi Akademik, Prestasi Non-Akademik